2007
DOI: 10.1021/la0633233
|View full text |Cite
|
Sign up to set email alerts
|

Individual Electrophoretic Mobilities of Liposomes and Acidic Organelles Displaying pH Gradients Across Their Membranes

Abstract: This report focuses on measuring the individual electrophoretic mobilities of liposomes with different pH gradients across their membrane using capillary electrophoresis with laser-induced fluorescence detection (CE-LIF). The results from the individual analysis of liposomes show that, using surface electrostatic theories and the electrokinetic theory as the first approximation, zeta potential contributes more significantly to the electrophoretic mobility of liposomes than liposomal size. For liposomes with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Subsequently, they demonstrated that different surface charge distributions and polarizabilities help predict the electrophoretic behavior of liposomes [9]. The effects of the pH gradients across the membrane of liposomes and acidic organelles on their electrophoretic mobilities were also investigated [7]. When the internal pH is higher than the external pH, the liposomes have more negative electrophoretic mobilities, which is consistent with a capacitive model.…”
Section: Bioparticle Electrophoresisfundamentalsmentioning
confidence: 66%
See 2 more Smart Citations
“…Subsequently, they demonstrated that different surface charge distributions and polarizabilities help predict the electrophoretic behavior of liposomes [9]. The effects of the pH gradients across the membrane of liposomes and acidic organelles on their electrophoretic mobilities were also investigated [7]. When the internal pH is higher than the external pH, the liposomes have more negative electrophoretic mobilities, which is consistent with a capacitive model.…”
Section: Bioparticle Electrophoresisfundamentalsmentioning
confidence: 66%
“…There has been some progress in developing theories that describe the electrophoretic mobility of bioparticles using liposomes as models [7][8][9]. Other work focusing on the use of liposomes as stationary phases, or earlier work on the analysis of liposomes by CE, has already been covered in two recent reviews [10,11] and is outside our scope.…”
Section: Bioparticle Electrophoresisfundamentalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using capillary electrophoresis with laser induced fluorescence detection it was shown that pH gradient across liposomal membrane induce electrophoretic mobility shifts based on capacity theory. Moreover, it was also proved that mobilities of acidic organelles are in congruency with predictions based on liposomal models (Chen et al, 2007). The major determinants of cytoplasmic rheology are fluid-phase viscosity and translational diffusion coefficient.…”
Section: Challenges Posed By Intracellular Environmentmentioning
confidence: 67%
“…The results indicated that zeta potential contributes more significantly to the electrophoretic mobility of liposomes than liposomal size (Chen and Arriaga, 2007).…”
Section: Capillary Electrophoresismentioning
confidence: 96%